Game Development of “Kwace Adat Bali” for The Socialization of Balinese Traditional Dress-Up Ethics - Cahya Dewi, Dewa Ayu Indah; Murpratiwi, Santi Ika (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2020)
Many young people have begun to violate the ethics of Balinese traditional dress up by using strict lacy blouse (kebaya), high split sarong (kamen), men sarong (kamen) that not taper on the tip and excessive accessories. Game of “Kwace Adat Bali” is expected as a means of socialization in Balinese traditional dress-up ethics appropriately. In this game, the Balinese traditional dress-up style is classified into three types, namely light traditional clothing (payas alit), middle traditional clothing (payas madya), and great traditional clothing (payas agung). The proposed method is Design Game Based-Learning Instructional Design (DGBL-ID) which is combined with a shuffle random algorithm to shuffle game items. The Game of “Kwace Adat Bali” has tested using alpha testing, beta testing, t-test, and game engagement questionnaire (GEQ). The alpha testing result was 100% game functionality has run suitable for the design. Beta testing shows that overall this game got a value of 77% from 65 respondents. There was a significant difference between user knowledge before and after playing the game of “Kwace Adat Bali” as indicated by t table value of 1.997, t value of 6.5, and the critical value of α = 0.05. The proposed method had an engagement rate of 8.7% higher than just using the DGBL-ID method in developing the game. Therefore, it can be concluded that the game feasible is considered as a new means of socialization in Balinese traditional dress up ethics for the younger generation.